Kliopsyllus schminkei sp. n. (Copepoda, Harpacticoida, Paramesochridae) a new copepod from the southeast Atlantic deep sea (Angola Basin) - Veit-Köhler, Gritta; Drewes, Jan (Zootaxa, 2009)
A new species of Kliopsyllus (Paramesochridae) has been collected with a multicorer from the abyssal Angola Basin in 2000 (on the DIVA-1 cruise, RV Meteor 48/1). Kliopsyllus schminkei sp. n. is the second most abundant Kliopsyllus- species in the Angola Basin and raises the number of valid members of the genus to 33. The new species is placed in the genus Kliopsyllus because of its typical segmentation and the setation of the swimming legs. K. schminkei sp. n. is unique within the genus and can be distinguished from the other species by a large apical pore on the P5 baseoendopodal lobes of the male, a length:width ratio of the furcal rami of 9 to 10:1 in both sexes, and an exceptional ratio of the length of the furcal rami to the whole body size of one fourth in the female and one fifth in the male. The new species is one of the four deep-sea Kliopsyllus-species described until now.